Answer:
g = -16
Explanation:
This is a "one-step" linear equation. To solve it, we need to have the coefficient of g be 1, not 3/4.
Since we know how to multiply fractions, we know that ...
(3/4)(4/3) = (3·4)/(4·3) = 12/12 = 1
That is, we can multiply both sides of the equation by 4/3 and that will give us a coefficient of 1 for g.
(4/3)(3/4)g = (4/3)(-12)
g = (4·(-12))/3 = -48/3 = -16
The solution is g = -16.
_____
The number 4/3 is the reciprocal of 3/4. It is found by swapping the numerator and denominator.